Blood, sweat and tears: androgenic-anabolic steroid misuse and recurrent primary post-tonsillectomy haemorrhage. (14th November 2014) - Fox, Richard; Varadharajan, Kiran; Patel, Bhavesh; Beegun, Issa
Abstract : A 30-year-old male body builder and androgenic-anabolic steroid and insulin abuser was admitted for day case elective tonsillectomy (bipolar). He returned with primary post-tonsillectomy haemorrhage 18 h after the operation and required bipolar cautery to the multiple small bleeding points in the right and left tonsillar fossa. Thorough coagulation screen was normal. Recurrent primary haemorrhage occurred 3 h post-operatively requiring immediate surgical intervention, removal of the inferior poles, precautionary throat packs, intubation and observation on the intensive treatment unit (ITU). Re-examination in theatre revealed a bleeding left superior pole that was under-run to achieve haemostasis and the patient returned to ITU. Hypertensive episodes were noted in the emergency department and intraoperatively including one recording >200 mm Hg. Haemostasis was eventually achieved once the blood pressure was adequately controlled. A slow wean of steroids was also instigated and the patient was managed on a surgical ward for 2 weeks post-tonsillectomy.